Reversible Notch1 acetylation tunes proliferative signalling in cardiomyocytes. Issue 1 (24th November 2017) - Collesi, Chiara; Felician, Giulia; Secco, Ilaria; Gutierrez, Maria Ines; Martelletti, Elisa; Ali, Hashim; Zentilin, Lorena; Myers, Michael P; Giacca, Mauro
Abstract: Aims: The Notch signalling pathway regulates the balance between proliferation and differentiation in several tissues, including the heart. Our previous work has demonstrated that the proliferative potential of neonatal cardiomyocytes relies on Notch1 activity. A deep investigation on the biochemical regulation of the Notch signalling in cardiomyocytes is the focus of the current research. Methods and results: We show that the Notch1 intracellular domain is acetylated in proliferating neonatal rat cardiomyocytes and that acetylation tightly controls the amplitude and duration of Notch signalling. We found that acetylation extends the half-life of the protein, and enhanced its transcriptional activity, therefore counteracting apoptosis and sustaining cardiomyocyte proliferation. Sirt1 acted as a negative modulator of Notch1 signalling; its overexpression in cardiomyocytes reverted Notch acetylation and dampened its stability. A constitutively acetylated fusion protein between Notch1 and the acetyltransferase domain of p300 promoted cardiomyocyte proliferation, which was remarkably sustained over time. Viral vector-mediated expression of this protein enhanced heart regeneration after apical resection in neonatal mice. Conclusion: These results identify the reversible acetylation of Notch1 as a novel mechanism to modulate its signalling in the heart and tune the proliferative potential of cardiomyocytes.